2009
DOI: 10.1111/j.1462-2920.2009.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of pH in determining the species composition of the human colonic microbiota

Abstract: The pH of the colonic lumen varies with anatomical site and microbial fermentation of dietary residue. We have investigated the impact of mildly acidic pH, which occurs in the proximal colon, on the growth of different species of human colonic bacteria in pure culture and in the complete microbial community. Growth was determined for 33 representative human colonic bacteria at three initial pH values (approximately 5.5, 6.2 and 6.7) in anaerobic YCFA medium, which includes a mixture of short-chain fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
453
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 622 publications
(487 citation statements)
references
References 52 publications
25
453
0
9
Order By: Relevance
“…Confirming previous results (15), Bt and Er are found to respond differently to changes in environmental pH values. Although Bt can grow faster than Er at neutral pH, Er has a less sensitive growth response to a drop in pH than Bt, and is thus less affected by the acidification caused by fermentative growth (Fig.…”
Section: Significancesupporting
confidence: 80%
See 1 more Smart Citation
“…Confirming previous results (15), Bt and Er are found to respond differently to changes in environmental pH values. Although Bt can grow faster than Er at neutral pH, Er has a less sensitive growth response to a drop in pH than Bt, and is thus less affected by the acidification caused by fermentative growth (Fig.…”
Section: Significancesupporting
confidence: 80%
“…1D). It has been shown that the pH dependence of these two strains is qualitatively representative of many abundant species in their respective phyla; Duncan et al (15) have tested 8 strains of the phylum Bacteroidetes, and 20 strains of the phylum Firmicutes at three different pH values, and consistently reported a less severe effect of low pH on Firmicutes. To model a coarse-grained gut microbiota composed of the two dominant phyla, the Bacteroidetes and the Firmicutes (6), we used the experimental parameters derived for Bt and Er ( Fig.…”
Section: Significancementioning
confidence: 99%
“…This in vivo enrichment of Firmicutes in mucus, although sometimes less strong as during our in vitro study, suggests that similar forces may drive the mucosal microbiota composition in vivo and in vitro, likely to include selection of specific groups that adhere to mucins (Leitch et al, 2007) or insoluble substrates in general (Walker et al, 2008). Furthermore, as opposed to the luminal content where the pH was maintained constant, local accumulation of acids in mucus may cause a lower pH, selecting for Firmicutes over Bacteroidetes and Proteobacteria (Duncan et al, 2009). In addition, mucins may also serve as a growth substrate for butyrate-producing Firmicutes, possibly via cross-feeding with mucin-degrading microbes that deliver partial breakdown products, acetate and/or lactate (Belzer and de Vos 2012), similar as reported for fructo-oligosaccharides (Belenguer et al, 2006;Falony et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the type of carbohydrate available to the microbiota, other factors also have to be considered with regard to propionate production in the gut. Thus, pH is an important determinant in the competition between Bacteroidetes and Firmicutes (Walker et al, 2005;Duncan et al, 2009), and the level of propionate production in Bacteroidetes is dependent on carbon dioxide levels (Macfarlane and Gibson, 1997).…”
mentioning
confidence: 99%